The Next Generation of Sustainable Food Packaging to Preserve Our Environment in a Circular Economy Context - Guillard, Valérie; Gaucel, Sébastien; Fornaciari, Claudio; Angellier-Coussy, Hélène; Buche, Patrice; Gontard, Nathalie (Frontiers in Nutrition, 2018)
Packaging is an essential element of response to address key challenges of sustainable food consumption on the international scene, which is clearly about minimizing the environmental footprint of packed food. An innovative sustainable packaging aims to address food waste and loss reduction by preserving food quality, as well as food safety issues by preventing food-borne diseases and food chemical contamination. Moreover, it must address the long-term crucial issue of environmentally persistent plastic wastes accumulation as well as the saving of oil and food material resources. This paper reviews the major challenges that food packaging must tackle in a near future to enter the virtuous loop of circular bio-economy and some solutions that are proposed to address the pressing international stakes in terms of food and plastic waste reduction and end-of-life issues of persistent materials. Production of microbial biodegradable polymers from agro-food waste residues seems a promising route to create an innovative, more resilient and productive waste-based food packaging economy by decoupling food packaging industry from fossil feed stocks and permitting nutrients to return to the soil. To answer the lack of tools and approach to properly design and adapt food packaging to food needs, mathematical simulation based on modeling of mass transfer and reactions into food /packaging systems are promising tools. Next generation of modeling and tools should permit to help the food packaging sector to validate usage benefit of new packaging solutions and chose in a fair and transparent way the best packaging solution to contribute to the overall decrease of food losses and persistent plastic accumulation.